ON THE USE OF SUNSPACE AND PCM FOR SPACE HEATING AND COOLING IN GREECE - Ms Eleftheria Dimopoulou (International Journal of Innovations in Engineering Research and Technology, 2021)
The present study examines the potential of improving thermal comfort conditions in a single room by means of passive solar systems, natural ventilation and phase change materials. The thermal performances of three different models are investigated on Energy Plus software for the cities of Athens and Thessaloniki, in Greece. To assess the contribution of each model on the thermal conditions of the residence space, a series of thermal comfort indicators were calculated, such as the intensity of thermal discomfort (ITD), the frequency of thermal comfort (FTC) and the fluctuation of discomfort (FD).